Telocyte-derived pentraxin 3 enables vascular pruning as a key driver in infantile hemangioma regression - Léa Pechtimaldjian; Marie-Laure Jullié; Chloé Rousson; Faiza Laanani; Julie Clachet; Yamina Idrissi; Maya Loot; Muriel Cario-Andre; Sorilla Prey; Alain Taieb; Christine Leauté-Labrèze; Thomas Mathivet; et al. (Proceedings of the National Academy of Sciences, 2026)
The natural course of infantile hemangioma (IH), a benign vascular infantile tumor, is marked by the initial rapid proliferation of dystrophic capillaries, followed by a regression phase, which is either spontaneous or induced by the first line treatment propranolol. Although endothelial cells have been at the center of most studies, the role of stromal cells in this vascular remodeling has remained unclear. Telocytes, which are stromal cells that may be targeted by propranolol, are involved in tissue organization and angiogenesis, suggesting their role in vascular remodeling during the regression of IH. To assess changes in vascular architecture of IH and the role of telocytes, we used Skin-iDISCO + 3-Dimensions (3D) sample imaging and in vitro models with patient-derived telocytes. Perivascular telocytes exhibited increased dendricity during regression, indicating their activation. Telocytes secretome profiling revealed a complex inhibitory program, with pentraxin 3 (PTX3) emerging as a central effector. 3D multicellular disease models demonstrated a paracrine effect blocking endothelial fibroblast growth factor receptors (FGFR) signaling via FGF2–PTX3 interaction, thereby strongly regulating endothelial proliferation, sprouting, and activation. In vitro mechanistic study and collagen IV staining analysis revealed that vascular regression is at least partially due to vascular pruning. These findings highlight the pivotal role of telocytes in orchestrating vascular remodeling during IH regression, opening therapeutic perspectives for inducing vascular normalization in pathological angiogenesis, including cancer.